P1835 Recognising extracardiac findings in cardiac imaging - a comparison between cardiologists and radiologists. (17th January 2020) - Sapiano, K; Borg, A
Abstract: Background: In the past, cardiac imaging modalities did not obtain much information about extracardiac structures. With the introduction of newer modalities such as CT and MRI, diagnostic quality images of structures surrounding the heart are now being obtained. This has led to the need for interpretation of images of extracardiac structures. Nowadays, this is being performed by cardiologists and radiologists; either separately or conjointly. Purpose: To evaluate whether there is any difference in the rate of positive extracardiac findings (ECF) between radiologists and cardiologists and to assess whether these ECF are of any clinical importance. Methods: All patients having had a cardiac MRI and cardiac CT performed in the year 2017 in a single centre were enrolled (n = 733). Reports of these images were reviewed retrospectively and information was obtained as regards to any differences in number of ECF picked up by cardiologists, radiologists or both working together. These ECF were then stratified according to their clinical importance and these subdivisions compared in the context of reporting physician. Results: A total of 733 scans were reviewed, 219 (29.9%) of these had positive ECF whilst 514 (70.1%) had none. Of the total amount, 314 (42.8%) were reported by cardiologists, 318 (43.4%) by radiologists and 101 (13.8%) jointly by both a cardiologist and a radiologist. Cardiologists found positive ECF in 18.2% of scans reviewed, radiologists reported findings in 37.4% of scans and, of those reported jointly, 42.6% were positive, p= <0.001. A pattern emerged where cardiologists found less clinically significant ECF with only 5.3% of findings classified as will definitely change management, in comparison to 19.3% by radiologists and 16.3% when reviewed jointly; and, only 15.8% of findings classified as will probably change management when compared to 23.5% by radiologists and 23.3% when reviewed jointly. However, it is important to note that this pattern was not statistically significant, p = 0.1432. Conclusions: A strongly statistically significant difference in the reporting of extracardiac findings has been highlighted in this article with cardiologists picking up less than half of extracardiac findings reported by radiologists. There was a pattern of cardiologists recognising less clinically important extracardiac findings, however this was not found to be statistically significant. These results should be reviewed with caution, taking into consideration the limitations of results obtained from a single centre. However, should this pattern keep repeating itself, one might consider increasing cardiologist training in ECF or having cardiac imaging reported conjointly by a cardiologist and a radiologist. Further studies are also necessary to ascertain the clinical relevance of the difference in ECF between cardiologists, radiologists or both specialists working together.